Survey of Fruit Flies (Diptera: Tephritidae) from 23 Species of Fruits Collected in Sleman, Yogyakarta - Valentina E. F. Aryuwandari; Y. Andi Trisyono; Suputa Suputa; Stefano De Faveri; Shanmugam Vijaysegaran (Jurnal Perlindungan Tanaman Indonesia, 2020)
Fruit flies (Diptera: Tephritidae) are major pests of fruits and vegetables in many countries, including Indonesia. Knowledge of the fruit fly host range in a specific area is an important part of the area-wide pest management program to reduce the pest problem. The aim of this study was to extend and update the information on the host range of fruit flies in the Regency of Sleman, Yogyakarta. This area is one of the centers of fruit production, particularly snake fruit in Indonesia. Fruit sampling was conducted from August 2019 to February 2020 in four sub-districts in Sleman consisting of different types of agro-ecosystems. Fruit rearing was carried out in the laboratory followed by identification of the fruit and fruit flies that emerged to species level. From the 23 species of fruits belonging to 14 different families that were collected, the following 6 species of fruit flies emerged: Bactrocera dorsalis, B. carambolae, B. umbrosa, B. albistrigata, B. mcgregori, and Zeugodacus cucurbitae. Bactrocera dorsalis and B. carambolae utilized the widest range of hosts, 12 and 11 species of fruits, respectively. Syzygium cumini, Malpighia emarginata, and Phaleria macrocarpa were recorded for the first time as new hosts of B. carambolae in Indonesia. Additional data of B. dorsalis and B. carambolae infesting salak cv. pondoh is also reported.